Tom Trueheart and the Land of Dark Stories - Beck, Ian. (New York : Oxford University, 2008)
Twelve-year-old Tom Trueheart, accompanied by his friend Jollity the crow, must journey to the dangerous Land of Dark Stories to rescue his brothers and their princess brides, and to try to defeat the villainous Ormestone once again.
Sequel to: The secret history of Tom Trueheart.
"First published in 2007 in Great Britain by Oxford University Press"--T.p. verso.
Keywords: Brothers -- Juvenile fiction; Brothers -- Fiction; Fairy tales -- Fiction